Polymorphisms and association of GRM1, GNAQ and HCRTR1 genes with seasonal reproduction and litter size in three sheep breeds. Issue 5 (8th February 2022) - Zhu, Mengting; Zhang, Hongmei; Yang, Hua; Zhao, Zongsheng; Blair, Hugh T.; Zhai, Manjun; Yu, Qian; Wu, Pei; Fang, Chenhui; Xie, Mengting
Abstract: Litter size is one of the important economic traits of livestock. Seasonal oestrus, ovulation and lambing of sheep have severely restricted the development of sheep farming in Xinjiang, China. The purpose of this study was to investigate the polymorphisms and genetic correlation between GRM1, GNAQ and HCRTR1 genes and the seasonal reproduction and litter size in three sheep breeds. The DNA mixed pool sequencing and PCR‐SSCP methods were used to detect single nucleotide polymorphisms (SNPs) of GRM1, GNAQ and HCRTR1 genes in seasonal oestrous (Kazakh and Chinese Merino [Xinjiang Junken type]) and perennial oestrous (Hu) sheep breeds. The association between genetic polymorphism and litter size was also analysed. The results showed that T945C in exon 2 of GRM1 gene, C589T in exon 2 of HCRTR1 gene and A191G in exon 2 of GNAQ gene were identified by Sanger sequencing, and three genotypes were existed in each SNP site, which all belonged to the synonymous mutation. GRM1 (CC), GNAQ (GA) and HCRTR1 (TC) were the dominant genotypes of seasonal reproduction and litter size in Kazakh sheep and Chinese Merino sheep, respectively, while, in perennial oestrous Hu sheep populations, the dominant genotypes were GRM1 (TC), GNAQ (GA) and HCRTR1 (TC), respectively, and association analysis also confirmed the results. The above results implied that GRM1, GNAQ and HCRTR1 genes are significantly associated with lambing traits in Kazakh, Chinese Merino and Hu sheep. Among them, the locus of GRM1 (T945C), GNAQ (A191G) and HCRTR1 (C589T) might be considered as a potential molecular marker, which controls seasonal reproduction and litter size in sheep.